At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Experience the convenience of getting reliable answers to your questions from a vast network of knowledgeable experts. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
Answer: The two solutions are x = -4 and x = -6
===========================================================
Explanation:
Cut the x coefficient (10) in half to get 10/2 = 5. Then square this to get 5^2 = 25.
We'll add 1 to both sides so that the "24" turns into "25", thereby completing the square
x^2 + 10x + 24 = 0
x^2 + 10x + 24+1 = 0+1
x^2 + 10x + 25 = 1
Notice on the left hand side we have something of the form A^2+2AB+B^2 where A = x and B = 5. We can factor this into (A+B)^2, which is the whole reason why we completed the square. You can use the FOIL rule to see how (A+B)^2 expands out into A^2+2AB+B^2. Factoring reverses this process.
This means x^2+10x+25 factors to (x+5)^2 and we now have these steps
(x+5)^2 = 1
x+5 = sqrt(1) or x+5 = -sqrt(1)
x+5 = 1 or x+5 = -1
x = 1-5 or x = -1-5
x = -4 or x = -6 are the two solutions
------------------
Let's check x = -4 to see if it works or not
x^2 + 10x + 24 = 0
(-4)^2 + 10(-4) + 24 = 0
16 - 40 + 24 = 0
-24 + 24 = 0
0 = 0
We get a true equation. That confirms x = -4 is a solution.
If we tried x = -6, then,
x^2 + 10x + 24 = 0
(-6)^2 + 10(-6) + 24 = 0
36 - 60 + 24 = 0
-24 + 24 = 0
0 = 0
That x value is confirmed as well.
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.